Risk of colonoscopy-related complications in a fecal immunochemical test-based population colorectal cancer screening program - Hsu, Wen-Feng; Chang, Chi-Yang; Chang, Chun-Chao; Chang, Li-Chun; Chen, Chien-Hua; Lin, Chun-Che; Lin, Yu-Min; Lee, Chia-Long; Wu, Hong-Yuan; Lee, Hsin-Chung; Lee, Yi-Chia; Su, Ming-Yao; Lin, Li-Ju; Chia, Shu-Li; Wu, Ming-Shiang; Chiu, Han-Mo; for the Colonoscopy Quality Assurance Joint Working Group of Taiwan Colorectal Cancer Screening Program and Digestive Endoscopy Society of Taiwan (Endoscopy, 2021)
Background The likelihood of advanced or synchronous neoplasms is significantly higher in fecal immunochemical test (FIT)-positive individuals than in the general population. The magnitude of the colonoscopy-related complication rate in FIT-positive individuals remains unknown. This study aimed to elucidate the colonoscopy-related complication rate after a positive FIT result and compare it with the rate when colonoscopy was performed for other purposes. Methods Information regarding colonoscopy-related severe complications after a positive FIT result (FIT-colonoscopy) and ordinary colonoscopy during 2010–2014 was collected from the Taiwanese Colorectal Cancer Screening Program Database and National Health Insurance Research Database. Severe complications included significant bleeding, perforation, and cardiopulmonary events ≤ 14 days after colonoscopy. The number of events per 1000 procedures was used to quantify complication rates. Multivariate analysis was conducted to assess the association of various factors with severe complications associated with FIT-colonoscopy compared with ordinary colonoscopy. Results 319 114 FIT-colonoscopies (214 955 patients) were identified, 51 242 (16.1 %) of which included biopsy and 94 172 (29.5 %) included polypectomy. Overall, 2125 significant bleedings (6.7 ‰) and 277 perforations (0.9 ‰) occurred ≤ 14 days after FIT-colonoscopy. Polypectomy, antiplatelet use, and anticoagulant use were associated with higher risk of complications (adjusted odds ratio [aOR] 4.41, 95 % confidence interval [CI] 4.05–4.81); aOR 1.35, 95 %CI 1.12–1.53; aOR 1.88, 95 %CI 0.61–5.84, respectively). Compared with ordinary colonoscopy, FIT-colonoscopy involved significantly higher risk of significant bleeding (aOR 3.10, 95 %CI 2.90–3.32).Conclusions FIT-colonoscopy was associated with a more than two-fold risk of significant bleeding, especially when polypectomy was performed.